An image-based modeling framework for patient-specific computational hemodynamics. - Antiga L; Piccinelli M; Botti L; Ene-Iordache B; Remuzzi A; Steinman DA; Antiga, Luca; Piccinelli, Marina; Botti, Lorenzo; Ene-Iordache, Bogdan; Remuzzi, Andrea; Steinman, David A (Medical & Biological Engineering & Computing, 2008)
We present a modeling framework designed for patient-specific computational hemodynamics to be performed in the context of large-scale studies. The framework takes advantage of the integration of image processing, geometric analysis and mesh generation techniques, with an accent on full automation and high-level interaction. Image segmentation is performed using implicit deformable models taking advantage of a novel approach for selective initialization of vascular branches, as well as of a strategy for the segmentation of small vessels. A robust definition of centerlines provides objective geometric criteria for the automation of surface editing and mesh generation. The framework is available as part of an open-source effort, the Vascular Modeling Toolkit, a first step towards the sharing of tools and data which will be necessary for computational hemodynamics to play a role in evidence-based medicine.